Perancangan Aplikasi E-Learning Pada SMP Swasta Arridha Dengan Menggunakan Bahasa Pemograman PHP dan Database Mysql - Putri, Ervantina; Ardi, Gus; Dedi, Purnama (Riset Sinergi Indonesia (RISINDO), 2022)
This study elaborated on the design of E - Learning at Junior High School Arridha using the programming language PHP. From the research that has been conducted at Junior High School Arridha can be concluded that the system was not effective because the learning process is still done on the condition that the face to face between teachers and students . After doing some research on Junior High School Arridha , collecting data through interviews and other methods. Then the analysis of data collected by the system design tools . After the designed output design , design input , design files and E -learning . The results of the analysis have been carried out on the website of E -Learning in the PHP programming language , and the new system is expected to be able to provide facilities in the learning process in the First State School for more effective and efficient.